2023
DOI: 10.1111/nyas.15090
|View full text |Cite
|
Sign up to set email alerts
|

Acquired preferences for a novel food odor do not become stronger or stable after multiple generations of odor feeding in Bicyclus anynana butterfly larvae

V. Gowri,
Antónia Monteiro

Abstract: Many herbivorous insects have specific host–plant preferences, and it is unclear how these preferences evolved. Previously, we found that Bicyclus anynana larvae can learn to prefer novel food odors from eating leaves with those odors and transmit those learned preferences to the next generation. It is uncertain whether such acquired odor preferences can increase across generations of repeated odor feeding and be maintained even in the absence of odor. In this study, we fed larvae with novel banana odor‐coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The phenomenon of memory persisting through metamorphosis, i.e., preimaginal memory persists into the adult form, has been reported in several insects, such as flies [30,31], parasitic wasps [32], moths [33], and ants [34]. Gowri and Monteiro [35] found that B. anynana larvae learned to prefer the novel odour within a generation of odour feeding and transmitted the learned preference to the next generation. We found the newly emerged T. limniace adults could maintain the memory experienced during the pupal stage.…”
Section: Discussionmentioning
confidence: 95%
“…The phenomenon of memory persisting through metamorphosis, i.e., preimaginal memory persists into the adult form, has been reported in several insects, such as flies [30,31], parasitic wasps [32], moths [33], and ants [34]. Gowri and Monteiro [35] found that B. anynana larvae learned to prefer the novel odour within a generation of odour feeding and transmitted the learned preference to the next generation. We found the newly emerged T. limniace adults could maintain the memory experienced during the pupal stage.…”
Section: Discussionmentioning
confidence: 95%
“…Bicyclus anynana is a subtropical model nymphalid butterfly that can learn preferences for novel visual cues [16,17] and transmit learned chemical cues to their offspring [8,18]. In previous studies, we showed that larvae that fed on an innate aversive odour, acquired a novel preference for that odour and produced naive offspring that inherited that odour preference [8,19].…”
Section: Introductionmentioning
confidence: 99%